The earth is weeping [compact disc, unabridged] : the epic story of the Indian wars for the American West - Cozzens, Peter, 1957- (HighBridge, a division of Recorded Books, 2016)
A history of the struggle between white forces and Native Americans over the fate of the post-Civil War West details the deconstruction of tribal culture, the conditions endured by frontier soldiers, and the ethical quandaries of military officials.